Application of the Coupled Eulerian Lagrangian method to the prediction of single‐grain cutting forces in grinding. Issue 1 (24th March 2023) - Furlan, Tim; Tsagkir Dereli, Tountzer; Schmidt, Nils; Biermann, Dirk; Menzel, Andreas
Abstract: Continuous technological advancements in the field of grinding technology and improved grinding tools have contributed to the development of high performance grinding processes. One example of such a process is internal traverse grinding (ITG) with electroplated cBN grinding wheels, where the tool consists of a conical roughing zone and a cylindrical finishing zone. Since the tool is fed in axial direction into a revolving workpiece, spindle deflections induced by varying process forces can lead to contour errors along the bore. Numerical simulations are a valuable tool to overcome the challenges associated with such high performance processes. Whenever spindle deflections need to be considered, accurate prediction of the process forces is paramount. Finite Element (FE) simulations have been widely used for the prediction of forces in cutting processes such as turning and milling, where only a small number of active cutting edges is considered, and where the geometry of these cutting edges is clearly defined. Grinding tools, on the other hand, contain a large number of grains with varying geometric characteristics. We recently proposed a multi‐scale simulation system for the simulation of ITG processes, where a geometric kinematic grinding simulation, based on a database of digitalised grains of a real grinding wheel, was used to determine the grain engagements [1]. The process forces were obtained from summation of the contributions of all active grains at any given time, based on a force model on the individual grain level. The force model takes the material removal rate and an approximation of the rake angle into account, and was calibrated via finite element simulations. In recent years, the Coupled Eulerian Lagrangian method (CEL), which is part of the commercial finite element software Abaqus, has been applied to simulate various cutting processes. No remeshing is necessary in this framework, and separation of chips from the workpiece can be modelled without element deletion. The application of CEL to the simulation of single grain cutting is therefore a promising approach to further improve the force model included in the process simulation of ITG. In this work, the kinematics of ITG are incorporated into a single grain cutting simulation, and the suitability of the CEL method for the problem is evaluated with a focus on the chip formation, separation and self‐contact between the chip and the workpiece.